The Amulets of German Merovingian Aristocracy - Dryakhlov, Vladimir; Kulakov, Vladimir (Archaeologia Lituana, 2018)
[full article, abstract in English; abstract in Lithuanian]The amulets referred to in this paper were found mainly in the eastern part of the Frankish tribal lands. There, in the Rhineland, Christianity did not hold as much ground in the 6th and 7th centuries as during later periods. Therefore, members of the Frankish aristocracy (a clear indication of the social strata the owners of the jewelry belonged to are the materials, i.e., precious metals, that the pieces were made of) preferred to rely on tried and tested amulets based on the native religious conventions rather than on Christian imagery (e.g., baptismal crosses).
Keywords: Merovingians; amulets; traditional cults; paganism; pagan relics